2010
DOI: 10.1016/j.nbd.2010.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposure to PCBs reduces striatal dopamine transporter densities only in women: A β-CIT imaging study

Abstract: We hypothesize that occupational exposure to PCBs is associated with a reduction in central dopamine (DA) similar to changes previously seen in PCB exposed adult non-human primates. To test that hypothesis we used [ 123 I]β-CIT SPECT imaging to estimate basal ganglia DA transporter density in former capacitor workers. Women, but not men, showed an inverse relationship between lipid-adjusted total serum PCB concentrations and DA transporter densities in the absence of differences in serum PCB concentrations. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 40 publications
0
29
0
Order By: Relevance
“…Twenty-eight years after termination of occupational PCB exposure, an inverse relationship between DAT and PCB levels was demonstrated in human females but not in males, showing that the PCB-sensitivity of human DAT may be gender-specific (Seegal et al, 2010). The DAT, which may be importantly involved in the pathophysiology of, e.g., ADHD (Bowton et al, 2014;Mergy et al, 2014), is subject to complex trafficking and posttranslational modifications, some of which are substrate-dependent (Zahniser and Sorkin, 2009).…”
Section: Presynaptic Molecular Mechanismsmentioning
confidence: 99%
“…Twenty-eight years after termination of occupational PCB exposure, an inverse relationship between DAT and PCB levels was demonstrated in human females but not in males, showing that the PCB-sensitivity of human DAT may be gender-specific (Seegal et al, 2010). The DAT, which may be importantly involved in the pathophysiology of, e.g., ADHD (Bowton et al, 2014;Mergy et al, 2014), is subject to complex trafficking and posttranslational modifications, some of which are substrate-dependent (Zahniser and Sorkin, 2009).…”
Section: Presynaptic Molecular Mechanismsmentioning
confidence: 99%
“…These findings are reported in Neurobiology of Disease 38, [219][220][221][222][223][224][225]2010 and are supported by epidemiological data demonstrating increased Parkinson's disease mortality, again only in women (Steenland et al, Epidemiology 17, 8-13, 2006).…”
Section: Introductionmentioning
confidence: 60%
“…223 R.F. Seegal et al / Neurobiology of Disease 38 (2010) [219][220][221][222][223][224][225] aromatase activity in the aging male may result in the loss of a neurorisk factor (i.e., central estrogen). For this hypothesis to provide a viable explanation for the sex differences in the effects of occupational exposure to PCBs on caudate and putamen β-CIT SPECT binding, it is necessary to posit that, if we had conducted the imaging study in younger, reproductively competent workers, we would have found that men would be more affected by PCB exposure than women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a mixture of Aroclors caused increased striatal dopamine autoreceptor (D2) sensitivity in male but not female adult rats [98]. Importantly, effects of PCBs on striatal DAT in human populations have also been found [99]. …”
Section: Effects Of Developmental Pcb Exposure On Social Behavior Andmentioning
confidence: 99%